2016
DOI: 10.1590/1516-4446-2015-1709
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and physical activity levels in outpatients with schizophrenia

Abstract: Objectives: To assess quality of life (QoL) and physical activity (PA) levels of outpatients with schizophrenia and healthy controls matched for age, gender, body mass index (BMI), hip circumference, waist circumference, and waist-to-hip ratio. Additionally, the present study investigated associations between PA levels, QoL, and anthropometric and behavioral measures among outpatients with schizophrenia. Methods: Thirty-two outpatients with schizophrenia and 32 individuals without mental illness were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 18 publications
1
14
1
1
Order By: Relevance
“…Previous studies have also found a negative correlation between quality of life and stigma in persons living with schizophrenia [37]. Studies have also found that the quality of life of persons living with schizophrenia is significantly better than that of outpatients [38]. In this study, there was almost no difference in subjective quality of life between community and hospitalized patients, which may be partly due to effective hospital-based mental health rehabilitation programs in Pudong New Area, Shanghai.…”
Section: Discussionsupporting
confidence: 46%
“…Previous studies have also found a negative correlation between quality of life and stigma in persons living with schizophrenia [37]. Studies have also found that the quality of life of persons living with schizophrenia is significantly better than that of outpatients [38]. In this study, there was almost no difference in subjective quality of life between community and hospitalized patients, which may be partly due to effective hospital-based mental health rehabilitation programs in Pudong New Area, Shanghai.…”
Section: Discussionsupporting
confidence: 46%
“…Previous research found that patients with schizophrenia had poorer QOL compared with healthy controls (Gomes et al, 2016;Sidlova et al, 2011). In addition, patients diagnosed with schizophrenia had lower QOL than patients diagnosed with other medical illnesses (Rai, Khess, Bhatacharjee, Gupta, &Koushal, 2014).…”
Section: Introductionmentioning
confidence: 96%
“…28 Furthermore, life style modifications such as; new psychosocial approaches, focusing on physical activities, weight and smoking management would help people with schizophrenia to improve their QoL. 29…”
Section: Discussionmentioning
confidence: 99%